If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-10x=1x-25
We simplify the equation to the form, which is simple to understand
6x-10x=1x-25
We move all terms containing x to the left and all other terms to the right.
+6x-10x-1x=-25
We simplify left and right side of the equation.
-5x=-25
We divide both sides of the equation by -5 to get x.
x=5
| 13+y=-3 | | -(3x-7)+6x=29 | | -13-5x=6-6x | | 9x^3+27x^2-x-3=0 | | 9x^3-19x^2-24x=0 | | -x+3=y-2-2 | | 0=10x^2-360 | | f+4=76 | | e*f-3m=x | | 5(10-6x)=200 | | (3t-8)(t-1)=0 | | -(r+7)+1=-3(-8r+2) | | 10(2x+4)=-1(-8-9x)+3 | | 2x-(3x+4)= | | x^2-2=18 | | 2mn= | | .7z+1.9+.1z=5.5-.42 | | 7x-65=43-2x | | -4(6x)= | | 5x+3(6x+15)=160 | | .0825t^2-.0924t+1.784=0 | | -12x=144 | | 1.2x+1.1=7.7-x | | 48=8 | | 18(x-1)+x=12-11x | | 3.75+7=8.1b-19.4 | | 3x+5-4x=7 | | (T-4)(t+1)=0 | | -17+3x=5x+7 | | 12w+w=5-2w | | 18+2y=4y-8 | | -2x-70=29+9x |